Comparative plastome analyses and evolutionary relationships of Drynaria - Chen, Xiao-Hua; Shu, Jiang-Ping; Li, Juan; Yan, Yue-Hong; Zheng, Xi-Long; Gu, Yu-Feng (Frontiers in Plant Science, 2026)
IntroductionThe genus Drynaria, a member of the Polypodiaceae family, exhibits substantial medicinal and ornamental value. Although molecular biological studies have elucidated the phylogenetic relationships in Drynaria, the characteristics of its plastome and the mechanisms underlying its adaptive evolution remain inadequately understood.MethodsThis study performed a comprehensive comparative genomic analysis based on the plastomes of 15 Drynaria species. The research analyzed codon usage bias and identified positively selected genes within this genus. A well-supported phylogenetic tree was constructed using plastome data, and divergence times were measured at key nodes.ResultsThe analysis revealed that the plastomes of the 15 Drynaria species varied in size from 151,473 bp (D. speciosa) to 163,438 bp (D. parishii), each with 133 genes. Comparative analysis demonstrated conserved gene content, order, and orientation across all examined species, with no inversions or rearrangements except for a non-coding region rearrangement in the large single copy region of D. roosii and the small single copy region of D. meyeniana. Nucleotide diversity analysis identified seven hypervariable regions. The study detected 691 simple sequence repeats, 136 tandem repeats, and 750 dispersed repeats. Codon usage bias in Drynaria plastomes was predominantly influenced by natural selection. Phylogenetic reconstruction based on complete plastomes produced congruent topologies. Divergence time estimation suggested that Drynaria originated in the mid-Paleocene (59.75 Ma), with major diversification events occurring during the late Miocene (6–5 Ma). Selection pressure analysis revealed positive selection of petA and ycf3 in branch models, while ccsA, ycf1, and rpoC2 exhibited evidence of positive selection in branch-site models.DiscussionThese findings provide insights into the evolutionary adaptations and genomic features of this ecologically and economically significant fern genus.